Engineered Streptomyces lividans Strains for Optimal Identification and Expression of Cryptic Biosynthetic Gene Clusters - Peng, Qinying; Gao, Guixi; Lü, Jin; Long, Qingshan; Chen, Xuefei; Zhang, Fei; Xu, Min; Liu, Kai; Wang, Yemin; Deng, Zixin; Li, Zhiyong; Tao, Meifeng (Frontiers in Microbiology, 2018)
Streptomyces lividans is a suitable host for the heterologous expression of biosynthetic gene clusters (BGCs) from actinomycetes to discover "cryptic" secondary metabolites. To improve the heterologous expression of BGCs, herein we optimized S. lividans strain SBT5 via the stepwise integration of three global regulatory genes and two codon-optimized multi-drug efflux pump genes and deletion of a negative regulatory gene, yielding four engineered strains. All optimization steps were observed to promote the heterologous production of polyketides, non-ribosomal peptides, and hybrid antibiotics. The production increments of these optimization steps were additional, so that the antibiotic yields were several times or even dozens of times higher than the parent strain SBT5 when the final optimized strain, S. lividans LJ1018, was used as the heterologous expression host. The heterologous production of these antibiotics in S. lividans LJ1018 and GX28 was also much higher than in the strains from which the BGCs were isolated. S. lividans LJ1018 and GX28 markedly promoted the heterologous production of secondary metabolites, without requiring manipulation of gene expression components such as promoters on individual gene clusters. Therefore, these strains are well suited as heterologous expression hosts for secondary metabolic BGCs. In addition, we successfully conducted high-throughput library expression and functional screening (LEXAS) of one bacterial artificial chromosome library and two cosmid libraries of three Streptomyces genomes using S. lividans GX28 as the library-expression host. The LEXAS experiments identified clones carrying intact BGCs sufficient for the heterologous production of piericidin A1, murayaquinone, actinomycin D, and dehydrorabelomycin. Notably, due to lower antibiotic production, the piericidin A1 BGC had been overlooked in a previous LEXAS screening using S. lividans SBT5 as the expression host. These results demonstrate the feasibility and superiority of S. lividans GX28 as a host for high-throughput screening of genomic libraries to mine cryptic BGCs and bioactive compounds.